A study to assess the prevalence of substance abuse and its impact among medical students in a medical college - Sharma, Aishwarya; Shashidhar, Manali; Maddali, Varshini Lakshmi Tripura; Rajiv, Srinivas; Shivanna, Mahima; Ramesh, Harshith (International Journal Of Community Medicine And Public Health, 2023)
Background: Psychoactive drug is an emerging global problem. This is a disturbing matter, especially in the case of medical students, affecting their health and academic performance, which in turn affects the health outcomes of patients. The objectives of our study were to assess the prevalence and impact of substance abuse among medical students. Methods: This was cross-sectional study conducted in tertiary care center. A pretested semi structured questionnaire was used to collect the data. Medical students who were available during the study period and who were willing to participate were included in the study. A total of 301 students were interviewed. Data was entered and analysed in SPPSS version 22.0. Descriptive statistics and inferential statistics were used for the statistical analysis. Results: We had a total of 301 responders. Among them, only 70(23.3%) have been a subject to substance abuse. Alcohol was the most abused substance (19.3%). The most common reason for starting these substances was out of curiosity (15.6%). 24.6% of the students have either thought of or tried stopping, however majority of them have not. Out of these students, 10 (3.3%) have experienced withdrawal symptoms. Conclusions: The substance abuse among youngsters in medical colleges is a highly alarming situation. Proper counselling with planned policies should be implemented to root out this evil among the future doctors which will help in providing better health care services to the people.